Economizing mind, 1870-2015 when economics and psychology met ... or didn't - Bianchi, Marina; De Marchi, Neil (History of political economy. Annual supplement, 2016)
Economists and psychologists share an interest in explaining how people make the choices that they do. However, economists have tended to stress individual rationality, shaped by economic motives and expressed in formal logical or mathematical models, while psychologists have preferred to identify influences through experimentation. In recent decades, behavioral economics has bridged the two fields and challenged the traditional economic assumption that individuals choose rationally. The essays collected here provide a longer view and reflect on episodic contact between psychology and economics beginning in the late nineteenth century. They help explain why meaningful, sustained joint inquiry eluded both disciplines for so long and usefully complement the recent inclination of researchers in each field to find inadequacy in the other.